The chemistry of heterocycles : chemistry of six-to-eight membered N, O, S, P and SE heterocycles - Ram, Vishnu Ji; Sethi, Arun; Nath, Mahendra; Pratap, Ramen (Elsevier, 2019)
The Chemistry of Heterocycles: Chemistry of Six to Eight Membered N, O, S, P and Se Heterocycles details the chemistry, behavior and potential of these important structures. The book presents a practical guide to international nomenclature, including discussions of fused ring systems, heteroatoms with abnormal valences, and bridged, spiro and polycyclic heterocycles. Three membered heterocycles are then the focus, along with their thermodynamic properties and importance in natural products, medicines, materials, and their unique aspects, such as strain, basicity and reactivity. Additional chapters cover 100 key heterocycle structures, from Azetidines, Pyrroles and Pyridines, to Benzoxepines and Oxocanes. Final chapters explore cutting-edge advances in the development of phosphorus and selenium based heterocycles.